Experience with Recording of Storm Waves, Swell and Tide Using an Inverted an Inverted Echo-Sounder off Durban (South Africa) - Jordaan, Jan M. (The International Hydrographic Review, 2015)
The paper describes the principle of continuous echo-sounding and recording of the undulating sea surface from a fixed point, by means of an acoustical pulse-transmitter-and-receiver situated on the sea floor on the continental shelf. The sounder is connected by submarine cable to the shore-based receiver. The procedure followed in installing and adjusting such an inverted echo-sounder off Durban and laying the cable to shore is briefly described. Features of the records obtained for a six month period, such as definition, accuracy, peakedness and multiple traces are discussed, and a summary of the results obtained for the recorded wave characteristics for Durban are given.